The influence of surgical technique on early posttransplant atrial fibrillation: comparison of biatrial, bicaval, and total orthotopic heart transplantation - Rivinius, Rasmus; Helmschrott, Matthias; Ruhparwar, Arjang; Erbel, Christian; Gleißner, Christian A.; Darche, Fabrice Fernand; Thomas, Dierk; Bruckner, Thomas; Katus, Hugo; Dösch, Andreas (Therapeutics and clinical risk management, 2017)
Purpose Early posttransplant atrial fibrillation (AF) has been associated with worse clinical outcomes after heart transplantation (HTX). The type of surgical technique may constitute a relevant risk factor for AF. Patients and methods This retrospective single-center study included 530 adult patients. Patients were stratified by surgical technique (biatrial, bicaval, or total orthotopic HTX) and early posttransplant heart rhythm (AF or sinus rhythm). Univariate and multivariate analyses were performed to evaluate risk factors for AF. Results A total of 161 patients received biatrial HTX (30.4%), 115 bicaval HTX (21.7%), and 254 total orthotopic HTX (47.9%). Sixty-one of 530 patients developed early posttransplant AF (11.5%). Patients with AF showed a statistically inferior 5-year survival compared to those with sinus rhythm (P<0.0001). Total orthotopic HTX had the lowest rate of AF (total orthotopic HTX [6.3%], bicaval HTX [14.8%], biatrial HTX [17.4%], P=0.0012). Multivariate analysis showed pretransplant valvular heart disease (P=0.0372), posttransplant enlarged left atrium (P=0.0066), posttransplant mitral regurgitation (P=0.0370), and non-total orthotopic HTX (P=0.0112) as risk factors for AF. Conclusion Early posttransplant AF was associated with increased mortality (P<0.0001). Total orthotopic HTX showed the lowest rate of AF compared to biatrial or bicaval HTX (P=0.0012).